Development of a Finnish Community of Game Scholars. (December 2013) - Harviainen, J. Tuomas; Lainema, Timo; Suominen, Jaakko; Soinila, Erno
In this editorial, we describe the emergence of a thriving Finnish community of game and simulation/game studies scholars. Central elements in this development were the coaching review system of Simulation & Gaming, scholars' intentional networking across traditional research paradigm lines, and a mentoring system that has helped beginning researchers hone their skills with the help of more experienced colleagues. As a result, Finland now hosts a vibrant simulation/game and game studies community, in which scholars from previously isolated paradigms work together.